Analisis Pengelolaan Sampah Akibat Pertumbuhan Penduduk dan Perkembangan Pembangunan di Kelurahan Cipare Kota Serang - Enggar Utari; Maudi Fatimatuzzahra; Mariana Pramaisyella; Siti Jaedah; Tiara Triana (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The purpose of this study is to analyze the impact of waste on the environmental conditions of the community, and to find out the proper management of waste due to massive population growth and development, as well as population activities that have an impact on domestic waste. This research belongs to the type of descriptive qualitative research, with data collection techniques by interviewing the Cipare Village, observation of research locations with assessment instruments that have been prepared, as well as secondary data obtained from Serang City in numbers. The conclusion of this research is population growth and development development have a very detrimental impact, especially on the environment around us, namely: garbage, excessive accumulation of garbage can cause various diseases, ecosystem imbalances, flood disasters because the flow of sewers is blocked by garbage, and inconvenience. in doing activities. Therefore, proper waste management must be carried out immediately to create a healthy environment. For this reason, local community participation is needed to carry out waste management properly and correctly, starting to sort out organic and inorganic waste, and also not to throw garbage indiscriminately.